Morphoanatomical and molecular characterization of two new Russula species in Section Ingratae from Pakistan - Razzaq, Annum; Naseer, Arooj; Shahid, Soumia; Khalid, Abdul Nasir (Phytotaxa, 2023)
Two new species in the genus Russula, viz. R. bhurbanensis and R. quercicola collected from coniferous forests in Khyber Pakhtunkhwa and Punjab provinces, Pakistan are described and illustrated. Russula bhurbanensis is characterized by its large-sized basidiomata with a viscid, orange to dark brown pileus, subglobose to broadly ellipsoid, medium-sized basidiospores having isolated to occasionally fused warts with rare line connections. Russula quercicola is characterized by medium-sized, orange to dark brown, hemispherical to infundibuliform pileus with incurved margins, globose and partially reticulate basidiospores with warts connected in long chains and thicker line connections. Some of the shared morphological features; like centrally depressed, viscous, dark brown pileus with tuberculate striated margins, adnexed lamellae, hollow stipe and unpleasant fotid odor confirm that both species belong to sect. Ingratae (subgenus Heterophyllidia) in Russula. Similarly, phylogenetic analyses of both species based on ITS and LSU sequences also proved their distinctive positions as two new species of Russula.